The Quality Measurement of Information System of Skill Competence Test Assessment at Islamic Vocational High School Pemalang by Using McCall Method - Indarta, Sandi Novyan; Hudallah, Noor; Khumaedi, Muhammad (Journal of Vocational and Career Education, 2021)
The measurement of information system of UKK assessment at Islamic Vocational High School Pemalang was done to measure the quality of the implementation of UKK assessment information system based on the user’s perception by using McCall method. The process of UKK assessment information system measurement at Islamic Vocational High School Pemalang was done with some stages of measurement by using some quality factors in McCall method, they are: correctness, usability, integrity, reliability, and efficiency to know how good the quality is and the quality of utilization of UKK assessment information system user. The measurement process was using 66 users where the result of this application was 78,6% and it was considered in a good category. However, further development was needed to improve the utilization of user and also to get better quality of UKK assessment information system.